NEEDS ANALYSIS FOR DEVELOPING AN INTEGRATED ETHNOSCIENCE BLENDED LEARNING INQUIRY MODEL IN THE BIOLOGY EDUCATION STUDY PROGRAM - Sari, Ermina; Martalasari, Martalasari; Awal, Raudhah; Afidah, Mar’atul; Wahyuni, Sri (Universitas Lancang Kuning, 2025)
One of the learning models that is still being implemented after the pandemic ends is blended learning. This study aims to analyze the needs of developing an Inquiry Blended Learning model integrated with ethnoscience in the biology education study program, Lancang Kuning University. The needs analysis in the development of this ethnoscience integrated Inquiry Blended Learning model is in the define phase in the 4D model development research (Define, Design, Develop, Disseminate). The method used is descriptive qualitative. The research instrument used was a questionnaire to analyze the needs of educators and students for the development of an inquiry blended learning model integrated with ethnoscience. The results showed the level of importance of this learning development obtained a kappa moment score from the student response of 0.90 and 0.81 (Very high category) from the lecturer's response. Based on these results it can be concluded that the development of Inquiry Blended Learning integrated with Ethnoscience is needed by students and lecturers in the Biology Education Study Program, Faculty of Education and Vocational Education.